2015 Systems and Information Engineering Design Symposium 2015
DOI: 10.1109/sieds.2015.7116981
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low-cost water treatment technology using <italic>Moringa oleifera</italic> seeds

Abstract: The persistent poor access to safe drinking water in low-income regions necessitates the development of low-cost alternatives to available yet expensive water treatment technologies. To address this need, this research investigates the development of a biofilter using the seeds of Moringa oleifera (MO), an indigenous tree in many low-income countries. The protein extracts from the MO seeds have been previously used as a disinfectant and coagulant in water treatment. However, the extraction of the protein leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Although the presented evidence is not sufficient for a concrete explanation, we hypothesize that a similar sequestration mechanism described in literature is displayed in these results [22][23][24][25]28], have revealed that the chemical structure of MOP suggests that the tail of this protein does not display any coagulation capabilities. This tail may have been the part of the MOP that attached to the surface of RHA and allowed MOP to be immobilized.…”
Section: Effect Of Contact Timesupporting
confidence: 61%
See 2 more Smart Citations
“…Although the presented evidence is not sufficient for a concrete explanation, we hypothesize that a similar sequestration mechanism described in literature is displayed in these results [22][23][24][25]28], have revealed that the chemical structure of MOP suggests that the tail of this protein does not display any coagulation capabilities. This tail may have been the part of the MOP that attached to the surface of RHA and allowed MOP to be immobilized.…”
Section: Effect Of Contact Timesupporting
confidence: 61%
“…MO protein saturation on the surface of RHA was achieved by soaking RHA in known concentrations of MO solutions (400-1700 mg/L). Sorption equilibrium was observed by reading initial and final equilibrium concentrations of MO proteins in solution at 280 nm [25].…”
Section: Preparation Of Moringa-functionalized Rice Husk Ashmentioning
confidence: 99%
See 1 more Smart Citation